Asymmetries between convergence and divergence reveal tonic vergence is dependent upon phasic vergence function - Erkelens, Ian M.; Bobier, William R. (Journal of vision (Charlottesville, Va.), 2017)
Horizontal vergence eye movements are controlled by two processes, phasic and slow-tonic. Slow-tonic responses are hypothesized to be stimulated by the faster, pulse-step neural output of the phasic system. This suggests that the general behavior of each system should be similar; however, this relationship has yet to be investigated directly. We characterize the relationship between phasic and tonic vergence by quantifying directional asymmetries in the response properties of each mechanism to the same disparity amplitudes. Four subjects viewed symmetric steps in disparity dichoptically at 40 cm while eye movements were recorded with infrared oculography. First- and second-order phasic and slow-tonic convergence response properties increased linearly with disparity demand (p < 0.01), whereas divergence responses did not (p > 0.05). Phasic divergence responses were slower than convergence (p = 0.012) and were associated with a higher frequency of saccades (p < 0.001). The average rate of slow-tonic change was correlated to the average peak velocity of phasic vergence at the same vergence demand in both directions, r = 0.78, p < 0.0001. Clear directional asymmetries were observed in phasic and tonic vergence responses. The response properties of the slow-tonic mechanism varied directly with the peak velocity of the complementary phasic system. These results provide empirical evidence of the relationship between phasic and slow-tonic vergence, suggesting that the latter depends on the motor function of the former, specifically the peak velocity. The recruitment of additional oculomotor mechanisms, such as saccades, improved the phasic response properties of the slower divergence mechanism but did not directly influence the response behavior of the slow-tonic mechanism.